Dog park use: Perceived benefits, park proximity, and individual and neighborhood effects. (26th May 2020) - Gómez, Edwin; Malega, Ron
Abstract: The purpose of this study is to explore the nature of dog park use and the role that perceived dog park benefits, park proximity, and both individual and neighborhood characteristics play in predicting dog park use. Factor analysis supported two dimensions of perceived benefits from dog parks (i.e., dog benefits and people benefits), which were used as composite variables in analyses. In addition to individual-level data gathered from the sample, this study used distance-related variables (e.g., street network approach to distance, buffer rings) computed from a Geographic Information System and socioeconomic neighborhood-level variables (e.g., percentage White in the neighborhood, home ownership) obtained from census tract data. Group differences, based upon park use, are explored with respect to both dog and people benefits. Logistic regression is used to predict dog owners' likelihood of using a fenced dog park.